Effects of Lactobacillus acidophilus and Propionibacterium freudenreichii on growth performance and carcass characteristics of finishing beef cattle - M.A. Greenquist; B. Dicke; G.E. Erickson; T.J. Klopfenstein; James S. Drouillard (Kansas Agricultural Experiment Station Research Reports, 2004)
There have been contradicting reports of the efficacy of direct-fed microbials in finishing cattle diets. Some researchers have observed improvements in daily gain and feed efficiency when direct-fed microbials are included in finishing diets, whereas others have reported no differences in dry matter intake or ruminal and blood pH. Many of these studies have been conducted on a relatively small scale and used few animals per pen compared with that of typical commercial feedlot operations. In our study, yearling crossbred beef steers and heifers (n=3,539; 796 lb body weight) were used in an experiment conducted at a commercial feedlot operation to characterize growth performance and carcass characteristics associated with the supplementation of direct-fed microbials (Lactobacillus acidophilus and Propionibacterium freudenreichii) in finishing cattle diets. Including direct-fed microbials in the diet throughout a 122-day finishing period had no measurable impact on growth performance or carcass characteristics of finishing cattle.
Keywords: Cattlemen' s Day; 2004; Kansas Agricultural Experiment Station contribution; no. 04-242-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 923; Beef; Lactobacillus acidophilus; Propionibacterium freudenreichii; Growth performance; Carcass characteristics; Finishing cattle